Macrophage Autophagy and Silicosis: Current Perspective and Latest Insights - Tan, Shiyi (Int J Mol Sci, 2021)
Silicosis is an urgent public health problem in many countries. Alveolar macrophage (AM) plays an important role in silicosis progression. Autophagy is a balanced mechanism for regulating the cycle of synthesis and degradation of cellular components. Our previous study has shown that silica engulfment results in lysosomal rupture, which may lead to the accumulation of autophagosomes in AMs of human silicosis. The excessive accumulation of autophagosomes may lead to apoptosis in AMs. Herein, we addressed some assumptions concerning the complex function of autophagy-related proteins on the silicosis pathogenesis. We also recapped the molecular mechanism of several critical proteins targeting macrophage autophagy in the process of silicosis fibrosis. Furthermore, we summarized several exogenous chemicals that may cause an aggravation or alleviation for silica-induced pulmonary fibrosis by regulating AM autophagy. For example, lipopolysaccharides or nicotine may have a detrimental effect combined together with silica dust via exacerbating the blockade of AM autophagic degradation. Simultaneously, some natural product ingredients such as atractylenolide III, dioscin, or trehalose may be the potential AM autophagy regulators, protecting against silicosis fibrosis. In conclusion, the deeper molecular mechanism of these autophagy targets should be explored in order to provide feasible clues for silicosis therapy in the clinical setting.